Changes in the distribution of surface sediment in Pearl River Estuary, 1975–2017, largely due to human activity. (1st October 2021) - Wei, Xing; Cai, Shuqun; Zhan, Weikang; Li, Yineng
Abstract: In recent decades, the surface sediments in the Pearl River Estuary (PRE), China, have been intensely disturbed by human activities. Data from 1975 to 2017 show that the mean surface sediment grain size in PRE is distributed between 5 and 8 ϕ, while the sorting coefficient of the sediments vary between 0.39 and 4.53, and the skewness is between −0.31 and 0.55. From 1975 to 1994, sandy sediment was mainly distributed near the outlets. However, sandy sediments have been present in the south of the West Shoal and Middle Shoal, and north of Lantau Island, and have had a patchy distribution since the 2000s. From 1975 to 2017, the average total grain size of the surface sediments in PRE changed from 6.4 to 5.3 ϕ, indicating a coarsening trend. This was mainly caused by the sharp reduction in upstream sediment load since the 1980s, as well as channel dredging and sand mining in PRE. On the one hand, the decrease in the sediment load caused an increase in the erosion area, which caused a large amount of fine-grained sediment to be eroded and transported to the open sea. On the other hand, channel dredging and sand mining resulted in coarse-grained sediments in the paleo-sedimentary layer being stirred to the surface, thus making a significant contribution to the coarsening of the average grain size. Channel dredging and sand mining are also the main reasons for the patchy distribution of sediments in PRE. In the future, with further reductions in the sediment load and the persistence of reclamation, channel dredging, and sand mining, the grain size of surface sediments in PRE will continue to show a coarsening trend. Highlights: The average grain size of the surface sediment in PRE showed a coarsening trend from 1975 to 2017. The sandy sediment has been distributed in patches in the estuary since the 2000s. The sharp reduction in sediment load and the dredging and sand mining in the estuary are the main reasons for these changes.